Planejamento e desenvolvimento racional de candidatos a fármacos inibidores de Influenza A - Medeiros, Herbert Igor Rodrigues de (2021)
RNA viruses have been a major problem for the entire world, given their easy replication, mutation and transmission. Specifically, influenza A is an RNA virus responsible for a high number of deaths, whether acting alone or aggravating several existing pathological conditions. Given the situation that this virus brings to the population and taking into account the few drugs used for the treatment of influenza A, it is extremely important to search for drug candidates that do not have as many side effects and that are effective for it, in alternative to current treatments, stressing the importance of candidates that act on multiple targets (multitarget), seeking through these, more effective and promising drugs, since, among the main advantages, it has the ability to block more than one target, obtaining better effectiveness and strength profiles. Thus, medicinal chemistry, through the use of computational tools, has been essential in the drug planning process, as it allows the optimization of time and operating costs. Associated with this, the growing number of cases resulting from endemic diseases, such as influenza A, has encouraged funding agencies to invest in research for the development of molecules that could be used in the treatment of such diseases. Thus, the aim of the present work was to propose natural molecules with potential anti-influenza A activity, predicted by a consensus analysis of three biological activity prediction models and analyzed by a hybrid virtual screening. In view of this, the database of 986 natural molecules were screened, first, through consensus analysis from 3 predictive models of biological activity, which resulted in only 36 molecules predicted to be active for influenza A and with excellent percentage of reliability, resulting from the construction of the 3 predictive models. Subsequently, these molecules were subjected to analyzes of the profile of absorption and oral bioavailability, risks of toxicity and metabolism against CYP 450. Molecular docking, against the 4 main proteins involved in the replication cycle of influenza A, namely: M2 channel, hemagglutinin, neuraminidase and RNA polymerase. With such results, in general all molecules showed excellent interactions against the 4 main proteins of influenza A, with emphasis on the HER03 molecule, which proved to be a potential drug candidate acting on multiple targets, considering the results that presented scores of interaction energies higher than for all control drugs and for all 4 proteins involved in the influenza A replication cycle. In view of these results, it was demonstrated that of the 986 natural molecules, 7 had potential to be drug candidates against influenza A, highlighting the HER03 molecule, which showed promising and potential results to be a candidate for an anti-influenza A drug acting on multiple targets.